1997
DOI: 10.1007/bf02426386
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal hernia repair

Abstract: In a prospective randomized trial comparing a totally pre-peritoneal (TPP) laparoscopic approach and the Stoppa procedure (open), loo patients with inguinal hernias (Nyhus IIIA, IIIB, IV) were followed over a 3-year period. Both groups were epidemiologically comparable. In the laparoscopic group, operating time was significantly longer (p=o.o1) but hospital stay (3.2 vs 7.3 days) and delay in return to work (17 vs 35 days) were significantly reduced (p=o.m). Post operative comfort (less pain) was better (p=o.o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In this study, laparoscopic hernia repair was in the beginning of the learning curve, hence it was expected to require skilled surgeons to avoid conversion rates, as in the institution surgeries are done by many budding surgeons. The mean duration of hospital stays in this study, in laparoscopic TEP repair group was 3.26days to that of open hernia repair group was 5.85days (p <0.0001) which was well correlated with studies of Champault G et al, who reported 3.2days in laparoscopic repair and 7.3days in open repair groups 17. The mean time to return to normal activity in the laparoscopic TEP repair group was7.18days to that in open repair group was 16.44days (p <0.0001).…”
supporting
confidence: 90%
“…In this study, laparoscopic hernia repair was in the beginning of the learning curve, hence it was expected to require skilled surgeons to avoid conversion rates, as in the institution surgeries are done by many budding surgeons. The mean duration of hospital stays in this study, in laparoscopic TEP repair group was 3.26days to that of open hernia repair group was 5.85days (p <0.0001) which was well correlated with studies of Champault G et al, who reported 3.2days in laparoscopic repair and 7.3days in open repair groups 17. The mean time to return to normal activity in the laparoscopic TEP repair group was7.18days to that in open repair group was 16.44days (p <0.0001).…”
supporting
confidence: 90%
“…A mentioned delay in passing urine was not included in the analysis. LA was used as an infiltration anesthesia with or without additional iliohypogastric and ilioinguinal nerve block and in- 12 43 -20/43 -Kark et al 19 3,175 0/3,175 --Callesen et al 20 1,000 0/995 -0/5 Abdu et al 24 400 0/400 --Beets et al 25 79 --1/79 Berliner et al 26 62 0/61 -0/1 Champault et al 27 100 --23/100 Cornell et al 28 60 --1/60 Davis et al 29 83 --5/83 Deans et al 30 150 --2/150 Dirkesen et al 31 175 68 2,559 --37/2,559 Prado et al 69 41 0/41 --Ramshaw et al 70 489 -0/47 20/442 Rutkow et al 71 2,403 -7/2,403 -Rutkow et al 72 2,886 -17/2,886 -Ryan et al 73 106 -19/106 -Sarli et al 74 115 --1/115 Sayad et al 75 512 --2/512 Spier et al 76 1 travenous sedation. Studies with additional LA combined with GA are listed as GA.…”
Section: Methodsmentioning
confidence: 99%
“…There have been reports of rare operative and postoperative complications and, because the procedure is technically demanding, several studies have described a long learning curve that included a high failure rate while surgeons were in this 'learning phase'. [115][116][117][118][119][120] Typically, the variables used to assess the learning curve of laparoscopic hernia repair have been operation time, recurrence rate and conversion to open surgery. There have been no firm recommendations on the number of procedures that should be performed before the learning curve is ascended.…”
Section: Laparoscopic Groin Hernia Repairmentioning
confidence: 99%
“…Liem and colleagues 116 indicated that most of the recurrences in their studies were among patients treated by a surgeon with 'limited experience' but do not go on to say how 'limited' was defined. Champault and colleagues 118 performed 50 procedures before including patients in their study, and the MRC Laparoscopic Groin Hernia Trial Group 115 required surgeons to have performed ten procedures before they could randomise patients. Again, there was no rationale given for the number of procedures chosen as the learning phase.…”
Section: Laparoscopic Groin Hernia Repairmentioning
confidence: 99%